Balloon-Blowing Exercises: Best Remedies for Lower Respiratory Tract Infections in Children - L. Lata, Kailash (International Journal of Nursing Research, 2024)
Background: Due to their rapid, children’s growth and development more exposed to the acute and long-term health consequences of pollutants in their surroundings, which can result in illnesses including diarrhea and respiratory tract infections. Objectives: The study’s objectives were to determine if balloon-blowing exercise has an impact on the lower respiratory tract characteristics in children aged 6–12 infections. Need: This study was to determine if balloon-blowing exercise has an impact on the lower respiratory tract characteristics in children aged 6–12. Nearly 1.0% of children had respiratory illness in 2019–2020 in Gujarat. Methods: The study used a quasi-experimental research design. Sample size: The sample comprises 60 kids who were hospitalized in a pediatric unit. They were diagnosed between the ages of 6 and 12 with lower respiratory tract infections. The research group received 30 of them, while the control group received 30. Sampling technique: For individuals who met the inclusion requirements for the study, the researcher chose a purposeful non-randomized sampling approach. Results: Pre-test and post-test mean values for the study group were 20.63 and 34.43, respectively. At P = 0.05, the paired t value of 15.76 is significant. It demonstrates that balloon-blowing activity was successful in easing respiratory discomfort. Hence, H1 was approved. While in the control group, children’s pre-test and post-test mean values for respiratory distress were 21 and 32.13, respectively. At the significance level of 0.05, the paired t value was 12.77 and was significant. Conclusion: According to the findings of the study, it was concluded that engaging in balloon blowing activities could have a positive impact on the respiratory parameters of children with lower respiratory tract infections.